2020
DOI: 10.5553/ijrj.000049
|View full text |Cite
|
Sign up to set email alerts
|

From ‘what works’ to ‘how it works’ in research on restorative justice conferencing: the concept of readiness

Abstract: While many empirical studies on restorative justice conferencing have been conducted in the context of 'what works', research on 'how it works' is scarce. Little is known about how, in what conditions and for whom restorative justice conferencing 'works'. In this article, I aim to fill this gap in the literature by developing a concept of readiness. It refers to participants' attitudes and emotional dispositions towards, and knowledge about, restorative justice conferencing and the other parties prior to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Nonetheless, this cycle is important to consider given that offenders do not necessarily participate in the RJ processes voluntarily (Abrams et al, 2006; Choi et al, 2010a; Zernova, 2007). As Suzuki (2020) demonstrated through his concept of ‘readiness’, some offenders attend RJ meetings for ‘self-regarding’ reasons such as avoiding harsher punishment. Even when offenders participate in the RJ processes for self-serving motivations, the victim’s generous gift of forgiveness may alter the offender’s attitude to the degree that they may be motivated to repay the victims (Kim and Gerber, 2012).…”
Section: Typology Of the Apology–forgiveness Cycle In Restorative Jus...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, this cycle is important to consider given that offenders do not necessarily participate in the RJ processes voluntarily (Abrams et al, 2006; Choi et al, 2010a; Zernova, 2007). As Suzuki (2020) demonstrated through his concept of ‘readiness’, some offenders attend RJ meetings for ‘self-regarding’ reasons such as avoiding harsher punishment. Even when offenders participate in the RJ processes for self-serving motivations, the victim’s generous gift of forgiveness may alter the offender’s attitude to the degree that they may be motivated to repay the victims (Kim and Gerber, 2012).…”
Section: Typology Of the Apology–forgiveness Cycle In Restorative Jus...mentioning
confidence: 99%
“…Addressing the under-investigated topic of the apology–forgiveness cycle will not only help to improve the quality of RJ practices, leading to further benefits, but such focus is also in line with the recent call for a research shift in RJ from ‘what works’ to ‘how it works’ (e.g. Lanterman, 2021; Suzuki, 2020) because we do not know how this cycle may or may not occur in the RJ meetings. Taken together, examining the apology–forgiveness cycle greatly adds not only to the literature on apology and forgiveness in RJ but also to the overall RJ literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research, among others: first, research conducted by Masahiro Suzuki (2020) found that the restorative justice process has the potential to alter participants' attitudes and behaviours. The concept of readiness can be used to examine the possibility of how the restorative justice process including preparation and follow-up does so.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to investigate whether and how the 'good' interaction between participants in restorative justice processes can help participants with low readiness move towards restorative outcomes. [5] Secondly, research conducted by Sahuri Lasmadi (2020) shows that the criminal justice system component consists of elements of the Police, Attorney General's Office, Court, and Correctional Institution as law enforcement officers. In applying the criminal justice system there are weaknesses and strengths.…”
Section: Introductionmentioning
confidence: 99%